KONTEKSTUALISASI NORMA FIKTIF POSITIF MENURUT UNDANG-UNDANG ADMINISTRASI PEMERINTAHAN - Wurid (Universitas Wiralodra, 2022)
The silence of the Government Administration as a Positive Fictitious Decision means thatif an Official and/or Government Agency ignores a request from a citizen, it is deemed to have granted the request. In Indonesia, Positive Fictitious Decisions have a place inlegislation. Law Number 30 of 2014 concerning Government Administration regulatesPositive Fictitious Decisions. This paper tries to explain the implementation of PositiveFictitious Decisions after the enactment of Law Number 30 of 2014 concerning Government Administration in the State Administrative Court.